Daily dynamic assessment and modelling of intersession processes in ambulatory psychotherapy: A proof of concept study. (8th November 2019) - Kaiser, Tim; Laireiter, Anton-Rupert
Abstract: Background : the typical mode of assessment in studies on intersession processes (ISP) in psychotherapy is using cross-sectional or weekly measurements. Daily dynamics of intersession processes have not yet been studied. Method : intersession process data from 22 ambulatory psychotherapy cases were collected in a naturalistic study with high temporal resolution, resulting in a total of 1026 daily measurements. Multilevel vector autoregressive (VAR) modelling was applied to discover the temporal course and causal influences among intersession processes. Centrality analysis was applied to discover unique functions of various intersession process variables. Results : a group-level network structure was discovered, offering first insights on the role of different intersession processes during psychotherapy. Centrality analysis revealed unique roles for various aspects of the intersession process. Temporal distance from the last session had only weak influence on the ISP. Conclusions : using short, daily measures, the unique role of various aspects of the ISP were uncovered. Some aspects of the ISP, like recalling session contents or reflection on future session contents, are facilitators of overall ISP intensity. Other aspects like thoughts on payment or appointments or negative treatment-related emotions are likely to suppress ISP.